Language Politeness on Mata Najwa’s Talk Show with Covid-19 Theme: Sociopragmatics - Maryanti Lucciana Sitorus; Umar Mono; Eddy Setia (Budapest International Research and Critics University, 2022)
This study aims to analyze language politeness on Mata Najwa’s talk show with Covid-19 theme based on sociopragmatic studies. The theory in this study is the theory of Brown and Levinson. Brown and Levinson's theory has 2 politeness strategies, namely positive politeness strategies and negative politeness strategies. This study used descriptive qualitative method. The data used in this study are the sentences contained in the conversational interactions between the presenter and the resource person. The source of the research data is the conversational interaction between the presenter and the resource person. The data collection technique in this study was the researcher working on the data already in the video and then analyzing it. The result of the research is that not all politeness strategies are found in conversational interactions on the Mata Najwa’s talk show. The result of the research is that using a group identity marker (positive politeness strategy) is more dominant than the question/fence strategy (negative politeness strategy).